Predicting consumer acceptability of crispy Pili Nuts based on sensory and physical attributes - Ciron, Christian Estoy 1976- (2004)
Abstract (Nine commercial crispy pili nut sample were evaluated by a trained panel and by 95 panelists (i.e., students and employees) from University of the Philippines Diliman. The samples were further instrumentally analyzed for color and hardness. Preference maps were constructed to provide a clear picture of the sensorial and instrumental profiles of the products. Preference mapping was used to interpret the preference patterns of the products. Using sensory and instrumental data, prediction models for acceptance of crispy pili nut samples were developed. These models allow for the prediction of acceptance of samples other than the ones studied. These also aid in the understanding and identification of the important sensory and physical characteristics that determine consumer acceptability of crispy pili nuts. The results of the study could be useful to the Philippine pili industry in improving and standardizing the quality of crispy pili nuts to be competitive in the international market).